Tiebout with Politics: Capital Tax Competition and Constitutional Choices. - Carlo Perroni; Kimberley A. Scharf (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
This paper examines how capital tax competition affects jurisdiction formation. We describe a locational model of public goods provision, where jurisdictions are represented by coalitions of consumers with similar tastes, and where the levels of taxation and local public goods provision within jurisdictions are selected by majority voting. We show that in this setting interjurisdictional tax competition results in an enlargement of jurisdictional boundaries, and can raise welfare for all members of a jurisdiction even in the absence of intrajurisdictional transfers.
Keywords: 330